Pelatihan Pembuatan Pakan Ternak Fermentasi Berbahan Baku Sumberdaya Lokal Di Kelompok Tani Ternak (KTT) Berlian Desa Sukadana - Endang Prasetyowati, Rini; Haryati Ningsih, Dwi; Wadi, Ikhwan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The purpose of this activity is training in special production technology for fermented feed using local resources such as straw and others. The implementation of preparation for community service activities includes: initial observation/survey activities, identification of potential and problems, preparing an action program plan, determining activities, coordinating and taking care of permits for all parties related to the service activities. The results obtained were that most group members did not utilize local raw materials for animal feed and they did not provide fermented animal feed for their livestock. Providing an understanding of the importance of the concept of increasing livestock production in the form of information transfer, knowledge about the concept of fermented animal feed related to its benefits and functions for increasing production carried out through FGD and lecture methods. During the discussion session, input and feedback were obtained from participants that could be useful for the implementation of the service process. The next session was a demonstration or practice of making fermented animal feed using local resources. In the follow-up stage, assistance was provided in providing fermented animal feed to each farmer's livestock, with the hope that the livestock would accept and eat the results of the fermented feed so that it could increase production and increase the income of livestock farmers. The implementation of community service activities went according to plan and could be realized according to expectations. In order to optimize and massively implement the activity of making fermented animal feed among livestock farmers, especially in the surrounding areas, the next community service activities were carried out in various community groups that could be directly affected by handling vulnerable animal feed.